(untitled) (Bangladesh Medical Journal, 2019)
Preterm low birth weight (LBW) babies are unable to control their body temperature and are at greater risk of illness. Kangaroo Mother Care (KMC) is special ways of caring for low birth weight babies. KMC provide thermal care through continuous skin to skin contact, support for exclusive breast feeding and early recognition and response to complication. The aim of the study is to assess thermal control, morbidities feeding pattern of baby getting KMC in comparison to conventional care. The study also give estimation about duration and cost during hospital stay and growth between the babies of two groups. This Randomized Controlled Trial was conducted in the Department of Neonatology, BSMMU, Dhaka from December 2012 to October 2013. Fifty neonate with birth weight 1250 to 1800 gm, gestational age >30 weeks to <37 weeks, Hemodynamically stable after birth were selected. Twenty five of them were randomly allocated to KMC(Group-I) and 25 of them to Standard Method Care (Group-II). The mother or care giver provided KMC at least 12hours/day in Group-I. Those in Group-II were managed under radiant warmer. During hospital stay both the groups were monitored and after discharge, the neonates were followed weekly till 40 weeks of corrected gestational age. There were no differences in birth weight, gestational age, number of male/female neonates, places of delivery and mode of delivery between two groups. During hospital stay hypothermia (Group-I 4% vs Group-II 24%) and hyperthermia (Group I 8% vs Group II 32%) were significantly low in KMC group. Late onset neonatal sepsis (LONS) developed significantly in Group-II. Though incidence of culture negative LONS did not differ in two groups but incidence of blood culture positive LONS was significantly high in standard care neonates (36% vs.0%; p=0.001). Neonates with KMC care required significantly shorter time to reach full feeding and to start direct breast feeding; also incidence of feeding intolerance was significantly lower in this group. After initial loss, weight gain started earlier as well as achieved the birth weight earlier in KMC group. Morbidities like hyperglycaemia and apnoea were significantly higher in standard care group. Neonates who received standard care stayed significantly longer in the hospital and total cost during hospital stay was also significantly higher in this group. At 40 weeks corrected gestational age, KMC infants showed significantly higher daily weight gain than standard care group. This study concluded that Kangaroo Mother Care provides effective thermal control, decreases the incidence of sepsis, improves feed tolerance, helps to achieving full enteral feeding and birth weight earlier in preterm LBW neonates. KMC enhances growth during postnatal period. KMC also found to reduce hospital stay and treatment cost. Proper implementation of KMC for the management of preterm low birth weight babies is safe and effective care. Bangladesh Med J. 2018 Jan; 47 (3): 1-8